Synergistic Effect of Different Plant Extracts and Antibiotics on Some Pathogenic Bacteria - Sharif, Suzan A.; Ismaeil, Abdulilah S.; Ahmad, Akhter A. (Science Journal of University of Zakho, 2020)
In this study, the antibacterial activity of methanol extract of henna (Lawsonia inermis) leaves, ethanol extract of pomegranate (Punica granatum) peel, volatile oil of sesame (Sesamum indicum) and peanut (Arachis hypogaea) were investigated against some Gram-positive and Gram-negative bacteria includingStaphylococcus aureus, Bacillus cereus, Escherichia coli and Acinetobacter sp. Henna extract was most effective substrate against all tested bacteria followed by pomegranate and peanut while sesame was less effective. All extracts were screened for their antibacterial activity in combination with commonly used antibiotics, including ciprofloxacin and erythromycin to evaluate synergistic effects using Minimum inhibitory concentrations (MIC) method which determined by microbroth dilution assays. Different interactions (synergistic and indifference) were observed between plant extracts and used antibiotics. The fractional inhibitory concentration (FIC) index ranged from 0.01 to 1.25 for B. cereus, 0.5 to 1 for P. aeruginosa, 0.01 to 0.3 for S. aureus and 0.06 to 0.25 for A. baumannii. The best synergistic capacity appeared between erythromycin and sesame. In vitro interaction between antimicrobial agents in combination with tested plant extracts showed synergistic effects. The MICs of each antibiotic was decreased to half when it is used in combination with tested plant extracts. This decreasing in MICs was observed in all plant extracts against tested bacteria as well as the extracts exhibited weak antibacterial activity alone.
Keywords: Antibacterial activity; Combination; Minimum inhibitory concentration (MIC); Plant extract; Synergistic